Effect of birth weight on adulthood renal function: A bias‐adjusted meta‐analytic approach. Issue 7 (July 2016) - Das, Sumon Kumar; Mannan, Munim; Faruque, Abu Syed Golam; Ahmed, Tahmeed; McIntyre, Harold David; Al Mamun, Abdullah
Abstract: While the association between low birth weight (LBW; <2500 g) and development of adult chronic renal disease (CKD) is inconsistently reported, less information is available regarding association of high birth weight (HBW; ≥4000 g) with CKD. We undertook a systematic review and meta‐analysis on studies published before 30 September 2015 and report associations between birth weight and renal function. Blood (glomerular filtration rate (GFR)) and urine (microalbuminuria/albumin excreation rate (AER)/urinary albumin creatinine ratio (ACR)) parameters were used to define CKD. Three different effect size estimates were used (odds ratio, regression coefficient and mean difference). The odds of developing CKD in the life course among those born LBW was 1.77 (95% CI: 1.42, 2.20) times and 1.68 (1.27, 2.33) times, assessed by blood and urine parameters respectively. Higher risk was also observed among Asian and Australian populations (blood: OR 2.68; urine: OR 2.28), individuals aged ≤30 years (blood: OR 2.30; urine: OR 1.26), and ≥50 years (blood: OR 3.66; urine: OR 3.10), people with diabetes (blood: OR 2.51), and aborigines (urine: OR 2.32). There was no significant association between HBW and CKD. For every 1 kg increase in BW, the estimated GFR increased by 2.09 mL/min per 1.73 m 2 (1.33–2.85), and it was negatively associated with LogACR (ß −0.07, 95% CI: −0.14, 0.00). LBW inborn had lower mean GFR −4.62 (−7.10, −2.14) compared with normal BW. Findings of this study suggest that LBW increased the risk of developing CKD, and HBW did not show any significant impact. Summary at a Glance: Findings of this study suggest that Low Body Weight increased the risk of developing CKD and High Body Weight did not show any significant impact. This is an interesting meta‐analysis.